A case report on primary hyperoxaluria type 1 in an infant - Bhatt, Jaladhi V.; Shah, Kanisha S.; Desai, Pankti; Paliya , Parag (International Journal of Contemporary Pediatrics, 2024)
An alanine-glyoxylate aminotransferase (AGT) deficiency causes elevated oxalate levels in primary hyperoxaluria type 1 (PH1), a rare genetic disorder that can cause renal complications. We report the case of a 3-month-old male infant with respiratory distress, decreased urine output, and metabolic acidosis who was born to consanguineous parents. Bilateral nephrocalcinosis and severe metabolic disturbances were found during further examinations. Prompt identification and genetic validation for therapeutic interventions guided by PH1, such as peritoneal dialysis. The severity of PH1 was highlighted by difficulties maintaining renal function even after an initial improvement. To lessen the severe effects of PH1, this case highlights the significance of early diagnosis, genetic evaluation, and multidisciplinary management.